Prognostic and predictive biomarkers for anti-EGFR monoclonal antibody therapy in RAS wild-type metastatic colorectal cancer: a systematic review and meta-analysis - Xiaona Lu; Yuyao Li; Yue Li; Xuemei Zhang; Jia Shi; Hai Feng; Zhuo Yu; Yueqiu Gao (BMC Cancer, 2023)
Abstract Background RAS mutations affect prognosis in patients with metastatic colorectal cancer (mCRC) and have been identified as strong negative predictive markers for anti-epidermal growth factor receptor monoclonal antibody (anti-EGFR mAb) therapy, but many tumors containing wild-type RAS genes still do not respond to these therapies. Some additional biomarkers may have prognostic or predictive roles, but conclusions remain controversial. Methods We performed a meta-analysis and systematic review of randomized controlled trials comparing anti-EGFR mAb therapy with alternative therapy that investigated the prognostic and predictive impact of additional biomarkers in RAS wild-type (wt) mCRC patients. Hazard ratios (HRs) and 95% confidence intervals (CIs) for progression-free survival (PFS) and overall survival (OS) and odds ratios (ORs) for objective response rate (ORR) were calculated. The prognostic value of biomarkers was investigated by separately pooling HR and OR for different treatment groups in an individual study. The predictive value was assessed by pooling study interactions between treatment effects and biomarker subgroups. Results Thirty publications reporting on eighteen trials were selected, including a total of 13,507 patients. In prognostic analysis, BRAF mutations were associated with poorer PFS [HRs = 3.76 (2.47–5.73) and 2.69 (1.82–3.98)] and OS [HRs = 2.66 (1.95–3.65) and 2.45 (1.55–3.88)] in both the experimental and control arms; low miR-31-3p expression appeared to have longer PFS and OS. In terms of predictive effect, a lack of response to anti-EGFR therapy was observed in patients with BRAF mutant tumors (P interaction < 0.01 for PFS). Patients with tumors with any mutation in the KRAS/NRAS/BRAF/PIK3CA gene also showed similar results compared with all wild-type tumors (P interaction for PFS, OS, and ORR were < 0.01, < 0.01 and 0.01, respectively). While low miR-31-3p expression could predict PFS (P interaction = 0.01) and OS (P interaction = 0.04) benefit. The prognostic and predictive value regarding PIK3CA mutations, PTEN mutations or deletions, EGFR, EREG/AREG, HER2, HER3, and HER4 expression remains uncertain. Conclusions In RAS wt mCRC patients receiving EGFR-targeted therapy, BRAF mutation is a powerful prognostic and therapy-predictive biomarker, with no effect found for PIK3CA mutation, PTEN mutation or deletion, but the combined biomarker KRAS/NRAS/BRAF/PIK3CA mutations predict resistance to anti-EGFR therapy. Low miR-31-3p expression may have positive prognostic and therapy predictive effects. Evidence on the prognostic and predictive roles of EGFR and its ligands, and HER2/3/4 is insufficient.